Prospective Study of Serum Uric Acid Levels and First Stroke Events in Chinese Adults With Hypertension - Hu, Feng; Hu, Longlong; Yu, Rihua; Han, Fengyu; Zhou, Wei; Wang, Tao; Zhu, Linjuan; Huang, Xiao; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Physiology, 2021)
Objectives: We investigated the association between serum uric acid (SUA) levels and the risk of first stroke in Chinese adults with hypertension. Methods: A total of 11, 841 hypertensive patients were selected from the Chinese Hypertension Registry for analysis. The relationship between SUA levels and first stroke was determined using multivariable Cox proportional hazards regression, smoothing curve fitting and Kaplan–Meier survival curve analysis. Results: During a median follow-up of 614 days, 99 case of first stroke occurred. Cox proportional hazards models indicated that SUA levels were not significantly associated with the first stroke event (adjusted-HR per SD increase: 0.98, 95% CI 0.76 to 1.26, P =0.889). In comparison to the group without hyperuricemia (HUA), there were no significantly higher risk of first stroke events (adjusted-HR: 1.22, 95% CI 0.79 to 1.90, P =0.373) in the population with HUA. However, in the population less than 60 years old, subjects with HUA had a significantly higher risk of first stroke than the population without hyperuricemia (adjusted-HR: 4.89, 95% CI 1.36 to 17.63, P =0.015). In subjects older than 60 years, we did not find a significant relationship between hyperuricemia and first stroke (adjusted-HR: 0.97, 95% CI 0.60 to 1.56, P =0.886). Survival analysis further confirmed this discrepancy (log-rank P =0.013 or 0.899 for non-aging or aging group). Conclusion: No significant evidence in present study indicated that increased SUA levels were associated with the risk of first stroke in Chinese adults with hypertension. Age played an interactive role in the relationship between hyperuricemia and the first stroke event.